Efficient Micropayment of Cryptocurrency from Blockchains. (2nd November 2018) - Rezaeibagha, Fatemeh; Mu, Yi
Abstract: Cryptocurrencies based on blockchain infrastructures have shown their advantages such as double-spending resistance and decentralization. Each transaction of cryptocurrency requires a certain amount of computation and attracts transaction fees. Often, in practice, many transactions are small; therefore, they add computation and transmission overheads to the system. In this paper, we introduce a cost-saving approach, which significantly reduces transaction time and storage for small amount of payment, i.e. micropayment. In our approach, with the notion of 'transaction commitment', the computation of each transaction is much more efficient. Therefore, our approach has advantages in comparison of other cryptocurrency systems such as the bitcoin system. Our approach can be applied to other existing cryptocurrency systems.